Representasi Video Iklan Layanan Masyarakat: "Stop Judi Online" Kejaksaan RI dalam Perspektif Psikologi Komunikasi - Sinaga, Roynanda; Pranata, Deddy; Ginting, Rahmanita (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
This study analyzes the representation of the public service advertisement video "Stop Online Gambling" by the Attorney General's Office of Indonesia from the perspective of communication psychology. The focus is on communication elements such as symbolism, narrative, color usage, and emotional expression used to deliver educational messages about the dangers of online gambling. Theoretical frameworks include fear appeal, social support, and linear narrative. Data were collected through observation and documentation and analyzed qualitatively using content analysis methods. The findings reveal that the video effectively conveys moral messages through a combination of strong symbolism, emotional approaches, and systematic narratives. Fear appeal creates a significant emotional impact, while social support is emphasized as a preventive measure against online gambling addiction. This study contributes to the development of more effective public communication strategies to address social issues in Indonesia.